2023
DOI: 10.3390/ijms24021318
|View full text |Cite
|
Sign up to set email alerts
|

Utility of High-Sensitivity Modified Glasgow Prognostic Score in Cancer Prognosis: A Systemic Review and Meta-Analysis

Abstract: The suitability of the high-sensitivity modified Glasgow Prognostic Score (HS-mGPS) in cancer patients remains unknown. We performed a systematic database search from 1 January 2010 to 30 September 2022, in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Selected studies reported the HS-mGPS and survival outcomes in cancer patients. The association between the HS-mGPS and survival outcomes was evaluated using a random-effects model and expressed as pooled haza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Some studies have demonstrated the utility of a combination of CRP levels and other serum markers (Table II). The Glasgow prognostic score (GPS), modified GPS (mGPS), and high-sensitivity mGPS (HS-mGPS) have been shown to predict oncological outcomes in several types of cancers, including STS (50)(51)(52). A combination of CRP levels and hypoalbuminemia was applied to these scoring systems.…”
Section: Prognostic Tool Using Crp For Predicting Survival In Stsmentioning
confidence: 99%
“…Some studies have demonstrated the utility of a combination of CRP levels and other serum markers (Table II). The Glasgow prognostic score (GPS), modified GPS (mGPS), and high-sensitivity mGPS (HS-mGPS) have been shown to predict oncological outcomes in several types of cancers, including STS (50)(51)(52). A combination of CRP levels and hypoalbuminemia was applied to these scoring systems.…”
Section: Prognostic Tool Using Crp For Predicting Survival In Stsmentioning
confidence: 99%
“…The Glasgow Prognostic Score (GPS), which includes C-reactive protein (CRP) and serum albumin, is a succinct prognostic tool that captures both the systemic inflammatory response and declining nutritional status [13]. The GPS has been extensively validated in oncology patients, and it has also been associated with chronic kidney disease (CKD) progression and mortality in prevalent Asian dialysis patients [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The modi ed Glasgow Prognostic Score (mGPS) is a validated predictive model for systemic in ammatory response (SIR), calculated based on Creactive protein (CRP) levels representing the level of in ammation and albumin levels representing the nutritional status [9]. Numerous studies have shown that increased GPS or mGPS level indicates poor prognosis in patients with mCRC, lung, oesophageal, and gastric cancers [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%